Weak-Form Market Efficiency of the Brazilian Exchange Rate: Evidence from an Artificial Neural Network Model - Palma, Andreza Aparecida; Sartoris, Alexandre [UNESP] (Taylor & Francis, 2016)
This article utilizes an artificial neural network model to examine the hypothesis of weak-form market efficiency for the monthly Brazilian exchange rate from 1999 to 2013. The method of partial derivatives suggested by Racine and White (2001) is used. The first step is to choose network architecture, second, weights estimation, and, at last, testing according to the suggested procedure. The results suggest that the Brazilian foreign exchange market is not efficient informally; thus, agents can obtain unusual profits through arbitrage.
Keywords: Artificial neural networks; exchange rate; inference; market efficiency